Induced variations by gamma radiation and EMS on the agronomic traits, essential oil yield with its quality and their exploitation in Java citronella (Cymbopogon winterianus Jowitt). (3rd August 2022) - Munda, Sunita; Begum, Twahira; Gogoi, Ankita; Pandey, Sudin Kr.; Sarma, Neelav; Lal, Mohan
Abstract: Purpose: The slips of Cymbopogon winterianus (Java citronella) are used to propagate this industrially important crop. It does not have a mating system that allows it to create new variability or develop superior progenies, which could be addressed by using induced mutation caused by physical or chemical agents. Physical treatments, rather than chemical treatments, are believed to be the most incredible alternative for mutation breeding. As a result, this study aims to assess the effects of gamma radiation and EMS treatment on the development of better C. winterianus progenies. Materials and methods: The three superior lines, i.e. JC-62 (IC-0627007), JC-55 (IC-0627000), and JC-71 (IC-0627018) based on high herbage, essential oil yield and citronellal content were selected through clonal selection during three-year evaluation. These were then irradiated with 60 Co gamma rays (50 Gy, 100 Gy, 150 Gy, 200 Gy, 250 Gy, and 300 Gy) and treated with EMS dose (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and 1%) separately. Ten plants of each dose were mutated and planted in the experimental field to obtain the MV2 progenies. After 4 months, the plants were harvested, and the slips were prepared and planted to get the MV3 and subsequently MV4 progenies. All morphological and essential oil data have been recorded and analyzed statistically. The essential oil was extracted through the Clevenger apparatus for all the progenies, followed by GC and GC-MS analysis. Results: The morpho-chemical study of the 112 healthy mutants has led to the identification of six superior progenies in MV4 progenies, M17, M63, M77, M179, M233, and M392. In terms of the economic yield, it was observed that mutant M77 treated with 0.20% EMS dose increased the herbage yield and citronellal content tremendously. In contrast, the progeny M17 irradiated with γ-100Gy increased essential oil yield from 1.32% to 1.50%. The EMS treatment at 0.10% and 0.20% doses showed an increasing trend in plant height, leaf length, tillers/bush, leaves/bush, herbage yield, and citronellal content compared to the base variety. The LD50 value of C. winterianus for gamma radiation and EMS treatment was averaged at 173 Gy and 0.72%, respectively. Conclusion: In C. winterianus, both gamma rays and EMS treatment successfully created superior progenies with desired characteristics. The 0.20 percent EMS treatment significantly improved economic features, including herbage yield and citronellal content. Simultaneously, gamma radiation at 100 Gy produced the highest essential oil yield, which is a highly desirable characteristic in C. winterianus breeding.